Work-life balance - Franz, Aisha, 1984- (Drawn & Quarterly, 2023)
"To achieve the proper work-life balance perhaps we just need the right therapist to coach us through our day-to-day. Anita, Sandra, and Dex have ambitions. Anita wants to move from making utility ceramics to fine-art sculpture but her pent-up dissatisfaction results in an outburst that puts her studio mate's work at risk. Sandra juggles her practical administrative day job at a startup with her wellness-influencer channel, finding both in jeopardy when a messy affair with a coworker comes to light. In another corner of the same startup, Dex's innovative ideas are rejected, leading him to spend his days hacking and working as a bike courier. All three are disillusioned with the daily grind. As the pressure for self-improvement builds, they end up looking to the same therapist for answers"--